STUDENTS’ RESPONSES ON USING WHATSAPP DURING ONLINE LEARNING - yuni amelia (English Tadris Department, Faculty of Tarbiyah and Teacher Training, State Islamic University (UIN) Datokarama Palu, 2021)
Recently, the use of mobile devices to communicate, learn, attain knowledge, and share information. Whatsapp as one of free downloaded device applications become the most popular platform, especially among university students. It is also regarded as one of teaching and learning media that could facilitate collaborative learning even though in this online classes due to Covid-19 pandemic. Challenges in attracting students’ attention and interest become higher during online learning, since lecturer could not directly interact and teach students. Students are required to fast adapt this new way. This research investigates students’ response on using Whatsapp as a learning tool during the online English Classes at State Islamic Institute of Palu. To get the result, there were 62 students of English Study Program at Tarbiyah and Teaching Education Faculty given 17 items of questionnaire. The result shows the majority of the students have positive responses and enjoy using Whatsapp as a learning tool during online classes. Even they love using Whatsapp.